Effect of Institutional Quality on the Financial Performance of Listed Firms in Nigeria - Surajdeen Tunde Ajagbe; Inelo J.O. (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2025)
Abstract The improvement of a company’s financial capability mirrors how adequately management utilizes firm resources. This provides investors information about the company’s general financial and economic well-being. Using a sample of 20 companies from 2012 to 2023, this study assesses the possible interconnection between institutional quality and the financial success of listed companies in Nigeria. The World Development Indicators' six governance metrics are used to evaluate the quality of institutions, especially those that deal with law enforcement and the reduction of official corruption. According to empirical findings from an ARDL panel analysis, the financial performance of Nigerian companies is positively but marginally impacted by the composite institutional index. This subtle positive link extends to specific indicators such as voice and accountability, government effectiveness, the rule of law, regulatory quality, and control of corruption. Conversely, the study indicated that both political stability and the rule of law surprisingly exert a significant and negative influence on the financial health of these businesses. From the analyzed data, it can be deduced that Nigerian companies' financial performance is a reflection of the widespread problem of low institutional quality. As a result, it is advised that the Nigerian government step up its efforts to improve institutional quality nationwide.